A systematic review of recovery high schools and collegiate recovery programs for building recovery capital among adolescents and emerging adults - Hennessy, Emily A.; George, Shane S.; Klein, Morgan R.; O’Connor, Jenny B.; Eddie, David; Kelly, John F. (Frontiers in Adolescent Medicine, 2025)
IntroductionEducational settings represent a prime opportunity for reaching adolescents and young adults (ages 12–27) experiencing substance use disorders (SUD). Recovery high schools (RHSs) were established to help adolescents in recovery finish their education while maintaining alcohol and other drug (AOD) abstinence and collegiate recovery programs (CRPs) were implemented for college and university students. With the continued proliferation of these programs, this review synthesizes the empirical literature on the impact of both types of educational recovery supports for youth.MethodThis review's methodology was based on a previous Campbell review on the same topic from 2017. We searched five public databases (May 2024), used PRISMA 2020 reporting guidelines, and followed Campbell Collaboration guidelines including Synthesis Without Meta-Analysis. Eligible studies focused on adolescent/emerging adult participants in RHSs or CRPs. Any outcome broadly related to SUD recovery was eligible. We included quantitative or mixed methods studies and allowed for cost-benefit/cost-effectiveness designs. Data from eligible studies were extracted in duplicate and assessed for quality (Quality Assessment Tool for Quantitative Studies) by four review team members. Two cost-benefit/cost-effectiveness studies included in the CRP review were rated for quality using a separate tool appropriate for these designs by a single reviewer.ResultsWe identified 37 manuscripts representing 25 unique studies focused on RHS (K = 7: N = 14,209) or CRPs (K = 18: N = 2,795). In the RHS studies, participants were predominantly White (41%) and females represented 29% of the sample. No studies met the criteria for low risk of bias. In the CRP studies, participants were predominately white (89%) and had slightly less female than male participants (45%). 11 of the 16 studies that did not use cost-benefit analysis were rated as high risk of bias. The quality rating of the two studies using cost-benefit designs indicated that both studies had fairly rigorous approaches.DiscussionThis research base suggests that students who participate in RHSs and CRPs may demonstrate reductions in AOD use, and improvements in social and academic outcomes, although given the existing research designs, statements about the incremental public health utility of investing in these programs relative to other approaches of equal intensity or duration cannot be made with confidence.